Successful rechallenge with cisplatin following cisplatin induced ischemic cerebrovascular accident in a patient with small cell lung cancer. Issue 10 (20th October 2022) - Rashid, Farah; Omar, Nabil E.; Aaekl, Hassan; Al Homsi, Ussama; Shablak, Alaaeldin
Abstract: Cisplatin is a widely used platinum‐based chemotherapy agent. Its common adverse effects are neuropathy, nephrotoxicity, electrolyte abnormality, and rarely causing thrombotic vascular toxicity. We present a patient known to have small‐cell lung cancer who developed ischemic cerebrovascular accident (CVA) after receiving chemotherapy regimen including cisplatin. Abstract : Cisplatin is rarely known to cause vascular toxicity resulting in thrombosis. Clinicians should be cautious of this side effect and act vigilantly if any patient presents with new onset neurological deficit or chest pain while he is on chemotherapy regimen consisting of cisplatin.